Islamic Religious Education Learning Trend in the Era of Revolution 4.0: Trend Pembelajaran Pendidikan Agama Islam Di Era Revolusi 4.0 - Muis, Andi Abd. (Procedia of Social Sciences and Humanities, 2024)
The advent of Revolution 4.0 has introduced significant transformations in educational paradigms worldwide, including Islamic Religious Education (PAI). This era is characterized by rapid technological advancements that have reshaped learning environments, necessitating educators to adapt and utilize sophisticated tools effectively. This study explores trends in PAI learning amidst Revolution 4.0, focusing on enhancing student quality and educator competencies through modernized teaching methodologies and digital learning tools.The background highlights the evolving role of technology in education and its impact on PAI, emphasizing the need for innovative approaches to maintain educational relevance and effectiveness. A specific gap in the literature pertains to understanding optimal strategies for integrating digital tools in PAI to foster both religious adherence and technological proficiency among students.